Renal Dimensions at Ultrasound in Adult Saudi Population - Naglaa M. Elsayed (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim of this study is to determine the normal range of renal measurements in healthy Saudi adults, and its correlation with their age, body mass index, height, side and gender by means of ultrasonography. Knowledge of the normal range of renal size is useful in appreciating variations that occur due to morbidities. Ultrasonography is an effective, easy and non invasive method to determine renal measurements. Ultrasonographic renal measurements were performed on 100 adult Saudi patients at the Radiology Department, King Abdulaziz University Hospital, Jeddah. The effect of age, gender, side, height and BMI were analyzed using Statistical Package for the Social Sciences. The average right renal length was 9.91 cm ± 0.85 and the left side was 10.17 ± cm 0.89, with the left renal length was significantly greater than right, and both renal lengths were greater in males than in females. Both kidneys' length correlated negatively with age and positively with BMI. No significant correlation between the renal length and personal height in either sex. The only significant factor affecting kidney width was BMI. Measurement of cortical thickness is less feasible. Expanded population-based studies are needed to establish normal renal values for Saudi population.